Features of the use of design technology at English lessons in primary school (Pedagogy of Higher and Secondary Education, 2013)
Pinchuk I. A. Features of the use of design technology at English lessons in primary school.The basic nature and the procedure of project using in the process of preschool pupils English teaching are characterized in the article. Project technology demands and project tasks in primary school are examined. The peculiarities of the main stages are described. Project technology importance is underlined.
Keywords: project technology; preschool pupil; English educational process in primary school; project presentation